L-methionine and the L-type Ca2+ channel agonist BAY K 8644 collaboratively contribute to the reduction of depressive-like behavior in mice - He, Ershu; Ma, Ruixue; Qu, Shanglan; Zheng, Xiaoye; Peng, Xin; Ji, Jieyu; Ma, Wenhao; Zhang, Xueyan; Li, Ying; Li, Hanwei; Li, Yanjiao; Li, Lijuan; et al. (Frontiers in Neural Circuits, 2024)
The L-type Ca 2+ channel (LTCC, also known as Cav1,2) is involved in the regulation of key neuronal functions, such as dendritic information integration, cell survival, and neuronal gene expression.Clinical studies have shown an association between L-type calcium channels and the onset of depression, although the precise mechanisms remain unclear. The development of depression results from a combination of environmental and genetic factors. DNA methylation, a significant epigenetic modification, plays a regulatory role in the pathogenesis of psychiatric disorders such as posttraumatic stress disorder (PTSD), depression, and autism. In our study, we observed reduced Dnmt3a expression levels in the hippocampal DG region of mice with LPS-induced depression compared to control mice. The antidepressant Venlafaxine was able to increase Dnmt3a expression levels. Conversely, Bay K 8644, an agonist of the L-type Ca 2+ channel, partially ameliorated depression-like behaviors but did not elevate Dnmt3a expression levels. Furthermore, when we manipulated DNA methylation levels during Bay K 8644 intervention in depression-like models, we found that enhancing the expression of Dnmt3a could improve LPS-induced depression/anxiety-like behaviors, while inhibiting DNA methylation exacerbated anxiety-like behaviors, the combined use of BAY K 8644 and L-methionine can better improve depressive-like behavior. These findings indicate that DNA methylation plays a role in the regulation of depression-like behaviors by the L- type Ca 2+ channel, and further research is needed to elucidate the interactions between DNA methylation and L-type Ca 2+ channels.